(untitled) (Journal of Informatics Education and Research, 2024)
This study explores the perspectives of teachers on the modifications brought about by the National Education Policy (NEP) 2020, which intends to restructure India’s educational framework with an emphasis on flexible and comprehensive learning. The study looks into how the educators feel about these revisions as well as how prepared they are to incorporate these adjustments into their teaching methods. A significant positive link was found between the views of educators toward the NEP revisions and their willingness to implement these changes in their teaching, according to a poll conducted among 88 educators. Important demographic variables, including prior teaching experience and educational background, have a substantial impact on attitudes and preparedness, according to statistical analysis. Higher qualified teachers or those with more years of experience in the field often demonstrated a stronger willingness and openness to accept NEP modifications (Debnath, et.al., 2024). The results of this study highlight how important it is to support educators in developing a positive mindset in order to guarantee the successful implementation of NEP 2020. The aforementioned findings suggest the necessity of ongoing professional growth and institutional assistance in order to improve the preparedness of educators and facilitate the shift to NEP-guided instruction.